Home sweet home glue casting as a visual representation for attachment - Caraos, Karisma Carmelle R.; Cabangis, Benjamin; Olazo, Jonathan Emmanuel (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
Home Sweet Home is an expression indicating alleviation and comfort upon retreating home, particularly after a lengthy interval. This paradoxical installation has the elements found in a home, yet the absurdity of the instability and impracticability of the material, lack f natural sunlight, and the lack of presence of inhabitants makes it less than appealing to be called "homely". Home Sweet Home is a title capsule wherein the past and present are captured, preserved; longing for the past, living in the present, but both do not radiate the comfort I yearn for. This strong desire to "feel at home"and to search for a perfect place has led me to create entirely the opposite.
Thesis (Bachelor of Fine Arts in Studio Arts)--University of the Philippines Diliman
Bibliography : leaves 44-46.
Keywords: Casts; Alienation (Social psychology)